QUALITY IMPROVEMENT IN EDUCATION (International Journal of Food and Nutritional Sciences, 2022)
The word education is imitative from Latin word 'educate' which means ' to rear ', ' to nourish', ' to bring up', ' to draw out ' etc. Its meaning has been drawn out by educationalist, philosophers as well as thinkers differently. They argue that education is about more than just learning facts; it's also about instilling values and teaching skills that will allow one to live a fulfilling life. India has long line of great men like Krishna, Budhdha, Mahavir, Nagarjun,and Chaankay who have taught about life in different ages. Whereas Mohammad, Jesus, Socrates, and Pluto, have made their meaning of education wide and different than that of others.India has very strong, globally praised system of education. Love for learning is such an early origin especially in higher level of learning, which has both social and individual relevance in India.